SIGNIFICANCE OF AHARA VIDHI VISHESH AYATAN IN THE MANAGEMENT OF NORMAL HEALTH (SPECIAL DIRECTION OF FOOD) - Pathak, S. K.; Kumar Rana, *Jitender (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda defines normal health as a balanced state of Doshas, Dhatus, Agni, mala and happiness of Atma, Indriyas and Manas as well as the physical mental and social wellbeing. According to WHOs definition of health â€œa state of physical mental and social wellbeing and not merely an absence of diseaseâ€. proper nutrition is very essential for healthy life. Ahara (food) is the main source of nutrition. Ahara (Food) sustains the life of living beings. All living beings in the universe require Ahara (food), complexion, clarity, good voice, longevity, geniusness, happiness, satisfaction, nourishment, strength and intellect are all conditioned by Ahara (food). Professional activities leading to happiness in this world, Vedic rituals leading to abode in heaven and observance of truth, Brahmhacharya leading to salvation are all based on food. Only the individual having a healthy body can afford to perform all activities leading to happiness, heaven and salvation, and for the preservation of health intake of food is essential. Hence food is the basic factor for the attainment of all of them. Ahara Vidhi Vishesha Ayatan (Eight types of special directions for ingestion of food). According to Acharya Charaka only the normal quantity of Ahara cannot provide the good result of Ahara because the result of Ahara depends upon Ahara, Vidhi, Vishesh, Ayatan Eight types of special direction have been given by Acharya Charaka for ingestion of food.